Aluminium recovery from waste incineration bottom ash, andits oxidation level. Issue 9 (September 2013) - Biganzoli, Laura; Grosso, Mario
The recovery of aluminium (Al) scraps from waste incineration bottom ash is becoming a common practice in waste management. However, during the incineration process, Al in the waste undergoes oxidation processes that reduce its recycling potential. This article investigates the behaviour of Al scraps in the furnace of two selected grate-fired waste-to-energy plants and the amount recoverable from the bottom ash. About 21–23% of the Al fed to the furnace with the residual waste was recovered and potentially recycled from the bottom ash. Out of this amount, 76–87% was found in the bottom ash fraction above 5 mm and thus can be recovered with standard eddy current separation technology. These values depend on the characteristics and the mechanical strength of the Al items in the residual waste. Considering Al packaging materials, about 81% of the Al in cans can be recovered from the bottom ash as an ingot, but this amount decreases to 51% for trays, 27% for a mix of aluminium and poly-laminated foils and 47% for paper-laminated foils. This shows that the recovery of Al from the incineration residues increases proportionally to the thickness of the packaging.